2013
DOI: 10.1007/s10803-013-1863-2
|View full text |Cite
|
Sign up to set email alerts
|

Virtual and Concrete Manipulatives: A Comparison of Approaches for Solving Mathematics Problems for Students with Autism Spectrum Disorder

Abstract: Students with autism spectrum disorder (ASD) are included in general education classes and expected to participate in general education content, such as mathematics. Yet, little research explores academically-based mathematics instruction for this population. This single subject alternating treatment design study explored the effectiveness of concrete (physical objects that can be manipulated) and virtual (3-D objects from the Internet that can be manipulated) manipulatives to teach single- and double-digit su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 32 publications
8
66
2
6
Order By: Relevance
“…Aligned with results of this study, Wong et al (2015) showed in the study that children with math learning disorder in comparison with healthy children have significant inhibition (18). Also other study showed significant difference between children with mathematics learning disorder and normal children in inhibition (19). It should be noted that selective attention is affected by inhibition and is associated with it because one who can't inhibit his behavior, distinguish intended stimuli among different stimulus and select it reflectively.…”
Section: Discussionsupporting
confidence: 82%
“…Aligned with results of this study, Wong et al (2015) showed in the study that children with math learning disorder in comparison with healthy children have significant inhibition (18). Also other study showed significant difference between children with mathematics learning disorder and normal children in inhibition (19). It should be noted that selective attention is affected by inhibition and is associated with it because one who can't inhibit his behavior, distinguish intended stimuli among different stimulus and select it reflectively.…”
Section: Discussionsupporting
confidence: 82%
“…Research is needed that will expand the limited numeracy research and provide the foundation for technology and math education for this population. Virtual manipulatives have been proven as an effective mode to provide math instruction to students with high-incidence disabilities and autism spectrum disorders (Bouck & Flanagan, 2010;Bouck, Satsangi, Taber-Doughty, & Courtney, 2014). Virtual manipulatives, delivered by way of a technology based interface (e.g., an iPad) can provide students a more cohesive mode to "manipulate" theme-based engaging materials.…”
Section: Future Researchmentioning
confidence: 99%
“…The work by Yakubova, Hughes and Shinaberry (2016) has shown the effectiveness of a video modeling intervention with CRA instructional sequence when teaching mathematics concepts to students with ASD. Some other intervention studies have successfully used virtual and concrete manipulatives to teach students with ASD arithmetic facts (Bouck, Satsangi, Doughty, & Courtney, 2014) and problem solving (Root, Browder, Saunders, & Lo, 2016).…”
mentioning
confidence: 99%